2021
DOI: 10.3390/jof7121062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Molecular Mechanisms of Resistance against DMI Fungicides in Cercospora beticola Populations from the Czech Republic

Abstract: Cercospora leaf spot (CLS), caused by the fungal pathogen Cercospora beticola, is the most important foliar pathogen of sugar beet worldwide. Extensive reliance on fungicides to manage CLS has resulted in the evolution of fungicide resistance in C. beticola worldwide, including populations in the Czech Republic. One important class of fungicides used to manage CLS is the sterol demethylation inhibitors (DMI). The aim of our study was to assess DMI resistance in C. beticola from the Czech Republic and elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Ergosterol is the most common sterol in fungi because it is an important component of the fungal cell membrane and is essential for fungal growth [ 51 ]. However, the resistance to DMIs has been identified in some phytopathogenic fungal species of Aspergillus , Fusarium , Rhynchosporium, Penicillium [ 52 , 53 , 54 , 55 ], Venturia nashicola [ 56 ], Villosiclava virens [ 57 ], and Cercospora beticola [ 58 ] for their ability to substitute some amino acids, such as CYP51, in the target protein. Future preliminary studies on the molecular characterization of mutational genes, such as CYP51A , CYP51B , and CYP51C , found in filamentous fungi resulting in amino acid substitutions that alter the structure of the CYP51 protein [ 59 , 60 , 61 ] are worth investigating as a tool to better elucidate the resistance mechanism of A. alternata .…”
Section: Discussionmentioning
confidence: 99%
“…Ergosterol is the most common sterol in fungi because it is an important component of the fungal cell membrane and is essential for fungal growth [ 51 ]. However, the resistance to DMIs has been identified in some phytopathogenic fungal species of Aspergillus , Fusarium , Rhynchosporium, Penicillium [ 52 , 53 , 54 , 55 ], Venturia nashicola [ 56 ], Villosiclava virens [ 57 ], and Cercospora beticola [ 58 ] for their ability to substitute some amino acids, such as CYP51, in the target protein. Future preliminary studies on the molecular characterization of mutational genes, such as CYP51A , CYP51B , and CYP51C , found in filamentous fungi resulting in amino acid substitutions that alter the structure of the CYP51 protein [ 59 , 60 , 61 ] are worth investigating as a tool to better elucidate the resistance mechanism of A. alternata .…”
Section: Discussionmentioning
confidence: 99%
“…lactucae-sativa is an airborne plant pathogen that can infect dozens of plants, and brassicaceae plants are one of its main targets [4,5]. The fungus is difficult to eliminate and can be resistant to fungicides due to its extensive reliance on fungicides [28]. Moreover, in organic farming, the incidence and severity of leaf spot disease on lettuce are regularly observed to result in a reduction in product quality and quantity [2].…”
Section: Discussionmentioning
confidence: 99%
“…After 6 days, isolates were transferred onto V8 agar (2% agar, 15% vegetable juice, 0,3% CaCO3) for conidial production. Isolates from 2021-2022 (all = 406) were from Austria (18), Czech Republic (24), France (106), Germany (51), Lithuania (24), Poland (115), Romania (20), Switzerland (18), Türkiye (9) and UK (21).…”
Section: Isolatesmentioning
confidence: 99%
“…A minor increase in EC 50 values in European populations was reported by Muellender et al (2021), who identi ed several point mutations in the DMI target gene sterol 14α-demethylase (CYP51). In addition to the detection of point mutations in the target gene that lead to an amino acid exchange (Kumar et al 2021; Muellender et al 2021), CYP51 overexpression (Nikou et al 2009;Muellender et al 2021), variable codon usage, and a silent mutation (Spanner et al 2021) have also been discussed as mechanisms for DMI adaptation in C. beticola. In their studies with isolates from the United States, Spanner et al (2021) reported that the phenylalanine of mutation L144F can be encoded by two different base triplets, TTT or TTC, both of which are associated with increased EC 50 values for tetraconazole.…”
Section: Introductionmentioning
confidence: 99%